若a^2+b^2=25,ab=12,求a^2-b^2
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/05 16:42:40
若a^2+b^2=25,ab=12,求a^2-b^2若a^2+b^2=25,ab=12,求a^2-b^2若a^2+b^2=25,ab=12,求a^2-b^2(a-b)^2=(a+b)^2-4ab=a^
若a^2+b^2=25,ab=12,求a^2-b^2
若a^2+b^2=25,ab=12,求a^2-b^2
若a^2+b^2=25,ab=12,求a^2-b^2
(a-b)^2=(a+b)^2-4ab=a^2+b^2-2ab=1
a+b=+-7
a-b=+-1
a^2-b^2 =(a+b)(a-b)=+-7
∵a²+b²=25,ab=12,
∴(a+b)²=a²+2ab+b²=25+2×12=49
a+b=7
(a-b)²=a²-2ab+b²=25-2×12=1
a-b=1
∴a²-b² =(a+b)(a-b)=7×1=7
若a/b=2,求分式a*a+ab-b*b/a*a-2ab+2b*b
若a^2+b^2=25,ab=12,求a^2-b^2
若a+b=3 ab=-2,求a+ab+ab+b的值
若a/b+b/a=3,求a^2+ab+b^2/a^2-ab+b^2的值
已知a+b=12,ab=20,求a(a+b)(a-b)-a(a+b)^2的值
已知a+b=12,ab=20,求a(a+b)(a-b)-a(a+b)^2的值
若a-b=3ab,求2a-ab-2b除以a+2ab-b的值
若a+b=3,ab=-2,求(5a-5b-ab)-(4a-6b-3ab)
a(a-1)-(a×a-b)=-5,求(a×a+b×b)÷2-ab
若a-b=4,ab=1,求(-2ab+2a+3b)-(3ab+2b-2a)-(a+4b+ab)的值
若a-b=4 ab=1 求(-2ab+2a+3b)-(3ab+2b-2a)-(a+4b+ab)的值
若a-b=4 ab=1 求(-2ab+2a+3b)-(3ab+2b-2a)-(a+4b+ab)的值
若集合{0,a^2,a-b}={1,a,ab}求b-a的值
已知a+2b=0,求a*a+2ab-b*b/2a*a+ab+b*b
设A={1,a,b},B={2,a^2,ab},若A=B,求实数a,b
已知:a^2+b^2=25,a+b=7,求ab和a-b
a+b=1,ab=-12,求a^2+b^2、a-b的值
若A=a+2b B=-b+3a 求2AB